Islamic Extracurricular Guidance for Students in Forming Noble Character at SDN 1 Lahat Selatan - Rita Yulia Anggraini; Amril Nurman; Fitriyana; Ferry Heryadi; Muhammad Al Fadjri (South Sulawesi Education Development (SSED), 2024)
This study aims to strengthen good teachers' character by cultivating students' noble morals, especially SDN 01 South Lahat Lahat Regency. In particular, Tanjung Payang Village, SDN 1 Lahat Selatan, uses qualitative descriptive methodology. Writing scientific articles helps students learn more while cultivating respectful behaviour and attitudes. These findings suggest that many students, particularly at SDN 1 Lahat Selatan, still lack the ability to use manners, preventing them from understanding how to do so per Islamic law. Based on the results of my teaching, I have found that teaching with qualitative descriptive methods and promoting Islamic principles is an effective way to help students develop moral character and become more respectful of their teachers and the wider community. The development of high moral principles, demonstrated by courtesy and respect for others and the environment, as well as the teaching strategies of those with high moral principles and knowledge of the subject, helps students become more morally upright.